Estimating the performance of wind turbines misaligned with respect to the wind direction using a simplified CFD based approach - Fitzgerald, Breiffni; Basu, Biswajit; Basu, Sudipta Lal (My University, 2024)
Wind direction in atmospheric boundary layer changes constantly. As such, the power extracted from the wind turbines in a wind farm is subjected to change. This change in wind direction impacts the wake pattern which in turn affects the power output of the downstream wind turbines. Empirical wind farm models are useful in such cases to assess the overall performance of the wind farms. However, the results provided by these models can be made more useful if fluid-structure interaction (FSI) effects are also considered. In the present work, we begin by looking at the potential flow model and the issues associated with it and used a modified model with constant vorticity to analyze the wind power available to the downstream wind turbines in a wind farm misaligned with respect to wind direction for irrotational flow. A simplified FSI based approach is used to carry out the simulations without the need of modelling the complicated wind turbine geometry.
The Science of Making Torque from Wind (TORQUE 2024)
PUBLISHED
Florence
Keywords: Smart & Sustainable Planet; COMPUTATIONAL FLUID DYNAMICS; Fluid Dynamics; Renewable energies; Wind Energy and Wind Turbines